Review of error correction for PUFs and evaluation on state-of-the-art FPGAs - Hiller, Matthias; Kürzinger, Ludwig; Sigl, Georg (Journal of cryptographic engineering, 2020)
Efficient error correction and key derivation is a prerequisite to generate secure and reliable keys from PUFs. The most common methods can be divided into linear schemes and pointer-based schemes. This work compares the performance of several previous designs on an algorithmic level concerning the required number of PUF response bits, helper data bits, number of clock cycles, and FPGA slices for two scenarios. One targets the widely used key error probability of 10 - 6 , while the other one requires a key error probability of 10 - 9 . In addition, we provide a wide span of new implementation results on state-of-the-art Xilinx FPGAs and set them in context to old synthesis results on legacy FPGAs.